Analisa Strategi Marketing Kreatif dengan Metode SWOT terhadap UMKM Sate Bandeng Hj Mariyam Serang Banten - Lala Lala; Khorihah Khorihah; Andi Suhandi; Mukhamad Riyadh; Riki Gana Suyatna (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
The purpose of this study was to analyze creative marketing strategy using SWOT on MSMEs of sate bandeng Hj. Mariyam. In this study using qualitative data types, and the data sources used are primary data and secondary data. The method used in this study is a SWOT analysis that analyzes strengths, weaknesses, opportunities and threats. From the results of this studystudy was to inform best strategy of creative marketing to get sale increase in sate bandeng Hj. Mariyam.